Case Report: MR-Guided Adaptive Radiotherapy, Some Room to Maneuver - Li, Winnie; Winter, Jeff; Padayachee, Jerusha; Dang, Jennifer; Kong, Vickie; Chung, Peter (Frontiers in Oncology, 2022)
Background A magnetic resonance linear accelerator (MR-Linac) provides superior soft tissue contrast to evaluate inter- and intra-fraction motion and facilitate online adaptive radiation therapy (ART). We present here an unusual case of locally advanced castrate-resistant prostate cancer treated with high-dose palliative ultra-hypofractionated radiation therapy on the MR-Linac with significant inter-fraction tumour regression. Case Presentation The patient was a 65-year-old male diagnosed with metastatic prostate cancer to bone and pelvic lymph nodes 7 years prior. At diagnosis, he presented with a PSA of 23 ng/mL and was commenced on a luteinizing hormone-releasing hormone agonist, achieving a PSA nadir of 4.68 ng/mL at 12 months. The patient subsequently had progressive lower urinary tract symptoms, his PSA increased to 47 ng/mL and there was a markedly enlarged pelvic mass involving the prostate with gross extra-capsular disease and invasion into the posterior bladder wall. The patient was referred for palliative radiation to the pelvic mass due to urinary symptoms, pain and lower limb paraesthesia. Treatment was planned to be delivered on the MR-Linac with a schedule of 36 Gy over 6 weekly factions allowing for maximal target dose delivery while minimizing surrounding organs at risk (OAR) radiation exposure. Unexpectedly, the target volume had a marked 49% (453cc to 233cc) reduction that was accounted for in the online adaptive process. A new reference plan was generated after 3 fractions to add sacral plexus as an OAR, previously not visible due to mass encroachment. The patient reported ongoing reduction in urinary symptoms, pelvic pain and lower limb paresthesia by the end of treatment. Conclusion Using daily MR-guided ART, improved visualization of the changing target and organs at risk ensured safe dose escalation. The unexpected positive response of the target and improved patient outcomes demonstrated the added value of the MR-Linac for on-line adaptive radiotherapy in this setting.